Bridging the gap between tight and loose contacts for soot oxidation by vanadium doping of cryptomelane nanorods catalyst using NO2 as an oxygen carrier. Issue 12 (7th June 2018) - Kaspera, Wojciech; Indyka, Paulina; Sojka, Zbigniew; Kotarba, Andrzej
Abstract : The effect of the V-doping of cryptomelane on bridging the tight-loose contact gap in NO-assisted catalytic soot oxidation was investigated. Abstract : The effect of the vanadium doping of cryptomelane K x Mn8 O16 nanorods (200 × 10 nm) on bridging the tight-loose contact temperature gap in NO-assisted catalytic soot oxidation was investigated. Catalysts with 0–20% vanadium content were synthesized and characterized in terms of chemical composition, structure, and morphology by means of XRF, XRD, XPS, RS, and TEM/EDX/SAED. Based on three catalyst surface–soot particles contact modes of catalytic measurements (tight contact, loose contact, and contactless), it was found that the incorporation of vanadium into the cryptomelane framework substantially increases the deSoot activity by promoting beneficial NO oxidation into NO2, with the strongest effect observed for 2.5% vanadium doping. The mechanistic role of NO in the kinetic coupling between ignition, catalytic combustion, and thermal afterburning is revealed, and the role of NO2 acting as an oxygen carrier from the catalyst to soot particles allows for the rationalization of the observed catalyst performance (lowering the temperature of 50% conversion in loose contacts by ∼100 °C). The results are discussed in terms of the catalyst–soot interface model, where a gradual loss of contact points during the combustion process (passing from tight to loose contacts) is substantially compensated by the in situ generation of NO2 controlled by the vanadium doping of the cryptomelane nanorods.